Pengaruh Model Project Based Learning Berbantuan Video Interaktif Terhadap Hasil Belajar IPAS Siswa - Arum, Liya Nofita; Fakhriyah, Fina; Hilyana, F. Shoufika (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study aims to determine the influence of the Project Based Learning (PjBL) model assisted by interactive video on the learning outcomes of Social Science of SD Negeri 1 Loram Kulon. This research is a quantitative research with an experimental method. The design of this study is One Group Pretest Posttest. The population in this study is all grade IV students. The sample in this study used saturated sampling of 19 students consisting of 5 women and 14 men. The data collection technique in this study is in the form of a test in the form of a description of 10 questions. The data analysis techniques used are normality test, linearity test, and hypothesis test. The results of the study showed that the results of the simple linear regression test showed a Sig value of 0.000 < 0.05 which means that the hypothesis was accepted and a determination coefficient test of 72% was obtained, which means that there was a positive influence of the use of the Project Based Learning (PjBL) model assisted by interactive video on the learning outcomes of IPAS SD Negeri 1 Loram Kulon.